2018
DOI: 10.1002/ardp.201800115
|View full text |Cite
|
Sign up to set email alerts
|

Novel cinnamic acid–tryptamine hybrids as potent butyrylcholinesterase inhibitors: Synthesis, biological evaluation, and docking study

Abstract: A novel series of cinnamic acid–tryptamine hybrids was designed, synthesized, and evaluated as cholinesterase inhibitors. Anticholinesterase assays showed that all of the synthesized compounds displayed a clearly selective inhibition of butyrylcholinesterase (BChE), but only a moderate inhibitory effect toward acetylcholinesterase (AChE) was detected. Among these cinnamic acid–tryptamine hybrids, compound 7d was found to be the most potent inhibitor of BChE with an IC50 value of 0.55 ± 0.04 μM. This compound s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…The treatment of Alzheimer's disease is of prime importance since the disease is characterized by memory loss, cognitive impairment and can be fatal. Treatment methods include restoring acetylcholine levels [56] and clearing the neurotoxic amyloid-beta protein [1]. Research has proven that cinnamic acid derivatives have neuroprotective ability and scientists keep on looking for neuroprotective agents based on cinnamic acid with better biological activity [6].…”
Section: Cinnamic Acid Derivatives With Neurological Activitymentioning
confidence: 99%
See 2 more Smart Citations
“…The treatment of Alzheimer's disease is of prime importance since the disease is characterized by memory loss, cognitive impairment and can be fatal. Treatment methods include restoring acetylcholine levels [56] and clearing the neurotoxic amyloid-beta protein [1]. Research has proven that cinnamic acid derivatives have neuroprotective ability and scientists keep on looking for neuroprotective agents based on cinnamic acid with better biological activity [6].…”
Section: Cinnamic Acid Derivatives With Neurological Activitymentioning
confidence: 99%
“…Compound 80l had a dual inhibitory potency and further studies showed that it exhibited good neuroprotective activity against Aβ 1-42 toxicity in PC12 cells and it can penetrate into the brain, which was observed in PAMPA-BBB assay in vitro making compound 80l a leading novel compound for the treatment of Alzheimer's disease [11]. Ghafary et al designed cinnamic acid-tryptamide hybrids (81a-l) (Scheme 4) and evaluated their inhibitory activity against acetylcholinesterace (AChE) and butylcholinesterace (BChE) ( Table 12) [56]. The presence of either an electron-donating or an electron-withdrawing group on position 4 of the unsubstituted tryptamine derivatives (81a-f) reduced the AChE inhibitory activity and the same effect was observed in compounds containing any substituent on the 4-position of the pendant benzyl group in the 5-methoxytryptamine series (81g-l), except for 81i.…”
Section: Cinnamic Acid Derivatives With Neurological Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…[26] Hence, in continuation to our interest in the development of potent anti-Alzheimer agents by molecular hybridization, in this work, a novel series of coumarin-3-carboxamide-N-morpholine hybrids 5a-5l has been presented ( Figure 1). [27] Herein, the synthesis, AChE/BuChE inhibitory effects, kinetic, and docking studies of these hybrids as new dual binding site ChE inhibitors are reported.…”
Section: Introductionmentioning
confidence: 99%
“…During the last years, compounds holding a cinnamoyl scaffold attracted attention because of their biological activities combined with low toxicity [3][4][5][6][7][8] . However, several of these compounds have also shown cytotoxic [9][10][11][12][13][14] as well as antimicrobial [15][16][17][18][19][20] and anti-oxidant properties [21][22][23][24][25][26] . Also, cinnamic acid derivatives have been used as valuable starting materials for the synthesis of peroxisome proliferatoractivated receptors (PPAR).…”
Section: Introductionmentioning
confidence: 99%